An exploration of human immunodeficiency virus (HIV) knowledge gaps among male migrant workers in Singapore - Ramsden, H.; Hopkins, Sandra (Academic Journals, 2012)
The general objective of this study is to provide a rapid assessment of HIV knowledge gaps among male migrant workers (MMWs) in Singapore. A cross-sectional pilot study was conducted in June 2011, in Singapore. A 14 multiple choice closed question self-administered questionnaire was used to collect information on current HIV knowledge among MMWs. Sixty seven MMWs participated in the survey and a total of 58 valid questionnaires were collected. Findings are reported by grouping survey responses of current knowledge of HIV. Although 84.5% of respondents have an awareness of HIV/AIDS, participants generally scored poorly in the survey and beliefs about the causes of HIV and HIV prevention strategies. 30.7% of those surveyed responded correctly to questions on HIV/AIDS knowledge, whilst 31.7% responded incorrectly and 37.7% of participants were unsure how to respond. The results indicate that there are significant HIV/AIDS knowledge gaps among male migrant workers in Singapore. We recommend that further research is required which could lead to the development of culturally appropriate peer-based HIV prevention programs, which should aim at both equipping this vulnerable group of individuals with necessary knowledge about HIV/AIDS and correcting misconceptions and misunderstandings.